2018
DOI: 10.1038/s41467-018-07910-7
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Probing molecule-like isolated octahedra via phase stabilization of zero-dimensional cesium lead halide nanocrystals

Abstract: The original version of this Article contained an error in the title, which incorrectly read ‘Probing molecule-like isolated octahedra via—phase stabilization of zero-dimensional cesium lead halide nanocrystals.’ The correct version states ‘via phase stabilization’ in place of ‘via—phase stabilization’. This has been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Surface of nanocrystals is essential to optimize their properties and performance in device applications, , in particular for materials like lead halide perovskites whose “easy to make, easy to break” nature is well known. Because of the successful use of nanocrystalline MAPbX 3 as the light harvester in solar cells, there has been enormous development of perovskite NCs of diverse compositions for employment in high-performance optoelectronic devices. All-inorganic cesium lead halide perovskite nanocrystals (PNCs) attract a lot of interest owing to demonstrations of the high photoluminescence quantum yield (PLQY), narrow emission linewidth, wide color gamut, intrinsic defect tolerance, and better chemical stability compared to their organic–inorganic counterparts. Their practical utilization nevertheless remains challenging as the structural integrity and the properties of the solution-processed nanocrystals exhibit degradation in solid films, as well as under the influence of environmental factors (humidity/heat/light). This instability is generally attributed to their soft ionic nature and labile surface . With isolation of [PbX 6 ] octahedra in crystal lattices, the development of lower dimensional perovskites, especially zero-dimensional (0D) Cs 4 PbBr 6 , has shown potential for improvement in stability and retaining high QY in the solid state compared to three-dimensional (3D) CsPbX 3 nanocrystals. The microscopic origin of the green emission in Cs 4 PbBr 6 is, however, still debated, and the material is not completely immune to environmental effects. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Surface of nanocrystals is essential to optimize their properties and performance in device applications, , in particular for materials like lead halide perovskites whose “easy to make, easy to break” nature is well known. Because of the successful use of nanocrystalline MAPbX 3 as the light harvester in solar cells, there has been enormous development of perovskite NCs of diverse compositions for employment in high-performance optoelectronic devices. All-inorganic cesium lead halide perovskite nanocrystals (PNCs) attract a lot of interest owing to demonstrations of the high photoluminescence quantum yield (PLQY), narrow emission linewidth, wide color gamut, intrinsic defect tolerance, and better chemical stability compared to their organic–inorganic counterparts. Their practical utilization nevertheless remains challenging as the structural integrity and the properties of the solution-processed nanocrystals exhibit degradation in solid films, as well as under the influence of environmental factors (humidity/heat/light). This instability is generally attributed to their soft ionic nature and labile surface . With isolation of [PbX 6 ] octahedra in crystal lattices, the development of lower dimensional perovskites, especially zero-dimensional (0D) Cs 4 PbBr 6 , has shown potential for improvement in stability and retaining high QY in the solid state compared to three-dimensional (3D) CsPbX 3 nanocrystals. The microscopic origin of the green emission in Cs 4 PbBr 6 is, however, still debated, and the material is not completely immune to environmental effects. ,, …”
Section: Introductionmentioning
confidence: 99%
“…There are also numerous reports which have shown an increase in the carrier lifetime and increase in the PLQY in Mn-doped CsPbCl 3 , thus making it a good candidate for photovoltaic applications. 56,57 Our studies provide useful insight into the origins of the long recombination lifetimes observed in Mndoped CsPbCl 3 underpinning a stabilized polaron formation. The clear experimental evidence of an activated phonon mode due to polaronic origin can be used as a marker to understand the structure and property relationship in these LHPs, which is fundamental for using them as potential materials for optoelectronic applications.…”
Section: Resultsmentioning
confidence: 88%
“…Overall, Mn doping stabilizes the polaronic mode, but the effects are more pronounced in Cl-rich systems than with Br incorporation. One of the previous studies by Arunkumar et al has shown that upon Mn doping between 5% and 10%, the covalent character increases in the (Pb/Mn)–Cl bond as opposed to the usual more electrostatic bond. As a result, the distortion in the lattice increases, which leads to polaron formation.…”
Section: Resultsmentioning
confidence: 93%